Salira Accelerates Perineal Wound Healing in Postpartum Mothers - Astri , Hetty; Fratidhina , Yudhia; Mulyati , Sri; Tulandy , Silvester Maximus (International Journal of Membrane Science and Technology, 2023)
Introduction: Bacterial infections during childbirth and puerperium are the leading causes of maternal death worldwide, accounting for about one-tenth of the global burden of maternal mortality; most of the 75,000 maternal deaths are estimated to occur worldwide each year; this is a direct cause of maternal mortality (WHO, 2015a). The incidence of infections that contribute to maternal mortality looks so concerning in Indonesia because Indonesia has the highest Maternal Mortality Rate (MMR) in ASEAN countries, namely 305 per 100,000 live births based on the 2015 Inter-Census Population Survey (SUPAS). This high maternal mortality rate makes the target of reducing MMR in Indonesia in the Sustainable Development Goals (SDGs) still very far from the target of 70 per 100,000 live births in 2030 (Achadi, 2019). Innovative efforts to reduce the incidence of infection during the puerperium need to consider the existing community structure in Indonesia. Problem-solving and the current situation of public health status in Indonesia are still based on a logical and rational approach, so health problems become increasingly complex. When a rational approach feels deadlocked in dealing with health problems, it is vital to raise local wisdom as a way to solve it, one of which is the use of herbal plants that are believed to be passed down by people in Indonesia, such as the use of red betel leaves. Researchers are interested in conducting innovative research using non-pharmacological methods for treating perineal wounds using (Salira), an ointment derived from red betel leaves formulated for wound healing; its use is only applied to the perineal wound. Besides the method, this technique is very cheap, easy, and safe to do. The red betel plant contains chemical compounds such as ß-flavonoids, alkaloids, saponins, tannins, and essential oils. This study aims to identify the relationship between the characteristics of the respondents (age, education, occupation, parity, and rupture rate) with the Perineum Wound Healing Time using Salira. Methods: The research method used in this study was quasi-experimental with a control group design. The independent variable in this study was red betel leaf ointment (Salira). In contrast, the dependent variable was the perineal wound healing time, as the confounding variable was the characteristics of postpartum mothers. The sample selection method used accidental sampling. The sample size in this study was 40 people for the intervention group and 40 for the control group. We collected data using questionnaires, checklist sheets, and observation sheets. Researchers also gave perineum care booklets to postpartum mothers and red betel ointment. Results: The results showed that red betel ointment was effective in accelerating the healing process of perineal wounds in postpartum mothers. Red betel ointment has anti-inflammatory and anti-bacterial properties, which can help reduce inflammation and infection of the perineal wound. In addition, red betel ointment can also help increase collagen production in wounds, an essential protein in the wound-healing process. The use of red betel ointment also does not cause significant side effects in postpartum mothers. This suggests that red betel ointment can be used as an alternative to perineal wound care that is safer and more effective than pharmacological drugs. Conclusion: Based on the results of existing research, it can be concluded that red betel ointment can help accelerate the healing process of perineal wounds in postpartum mothers. Red betel ointment has anti-inflammatory and anti-bacterial properties, which can help reduce inflammation and infection of the perineal wound. In addition, red betel ointment can also help increase collagen production in wounds, an essential protein in the wound-healing process.